An in vitro study evaluating the effect of ferrule design on the fracture resistance of endodontically treated mandibular premolars after simulated crown lengthening or forced eruption methods - Qingfei Meng; Qian Ma; Tianda Wang; Yaming Chen (BMC, 2018)
Abstract Background The purpose of this study was to evaluate the effect of ferrule design on the fracture resistance of endodontically treated mandibular first premolars after simulated crown lengthening and orthodontic forced eruption methods restored with a fiber post-and-core system. Methods Forty extracted and endodontically treated mandibular first premolars were decoronated to create lingual-to-buccal oblique residual root models, with a 2.0 mm height of the lingual dentine wall coronal to the cemento-enamel junction, and the height of buccal surface at the cemento-enamel junction. The roots were divided randomly into five equal groups. The control group had undergone incomplete ferrule preparation in the cervical root, with 0.0 mm buccal and 2.0 mm lingual ferrule lengths (Group F0). Simulated surgical crown lengthening method provided ferrule preparation of 1.0 mm (Group CL/F1) and 2.0 mm (Group CL/F2) on the buccal surface, with ferrule lengths of 3.0 mm and 4.0 mm on the lingual surface, respectively. Simulated orthodontic forced eruption method provided ferrule preparation of 1.0 mm (Group OE/F1) and 2.0 mm (Group OE/F2) on the buccal surface and ferrule lengths of 3.0 mm and 4.0 mm on the lingual surface, respectively. After restoration with a glass fiber post-and-core system and a cast Co-Cr alloy crown, each specimen was embedded in an acrylic resin block to a height on the root 2.0 mm from the apical surface of the crown margin and loaded to fracture at a 135° angle to its long axis in a universal testing machine. Data were analyzed statistically using two-way ANOVA with Tukey HSD tests and Fisher's test, with α = 0.05. Results Mean fracture loads (kN) for groups F0, CL/F1, CL/F2, OE/F1 and OE/F2 were as follows: 1.01 (S.D. = 0.26), 0.91 (0.29), 0.73 (0.19), 0.96 (0.25) and 0.76 (0.20), respectively. Two-way ANOVA revealed significant differences for the effect of ferrule lengths (P = 0.012) but no differences for the effect of cervical treatment methods (P = 0.699). The teeth with no buccal ferrule preparation in control group F0 had the highest fracture resistance. In contrast, the mean fracture loads for group CL/F2 with a 2.0-mm buccal and 4.0-mm lingual ferrule created by simulated crown lengthening method were lowest (P = 0.036). Conclusions Increased apically complete ferrule preparation resulted in decreased fracture resistance of endodontically treated mandibular first premolars, regardless of whether surgical crown lengthening or orthodontic forced eruption methods been used.